Genotoxic activity of 2-amino-N-hydroxylaminopurine (AHA) in Aspergillus nidulans - N. Babudri; G. Morpurgo; C. Checchi; S. Pimpinelli; A. Marini (Fungal Genetics Reports, 1995)
In Aspergillus nidulans, as well as in other eukaryotic cells, not all base analogs are mutagenic. For example, 2-aminopurine (2-AP) is non-mutagenic or weakly mutagenic for eukaryotes while it is mutagenic for bacteria. Because of their potential use in genetical research, an effort has been made to find base analogs mutagenic for eukaryotic cells. Work in this field has been successful: in fact, 6- hydroxylamino-purine (HAP) and 2-amino-N-hydroxylaminopurine (AHA) have been found mutagenic for yeast as well as for other eukaryotic cells. (Pavlov et al. 1991, Mut. Res. 253:33-46). In particular, Brockman et al. (Mut. Res. 177:61-75, 1987) tested the mutagenic activity of HAP and AHA in Neurospora crassa and found that AHA is about equally mutagenic as HAP at low doses but more mutagenic at high doses. In this paper we report the genotoxic activity of AHA in A. nidulans. In this mold, we have tested AHA-induced lethality and mutagenic and recombinogenic effects